Assessment of the Effect of Telephonic Follow-up on Readmissions and Mortality Rate of the Patients with Acute Coronary Syndrome and Acute Heart Failure in Rashid Hospital - Prabakaran, Mary Sumitha; Jamil, Naser; Thomas, Rose Mary; Mohanan, Mayamol; Jose, Anumol; Chandrabose, Akila Jeyasingh (Dubai Medical Journal, 2024)
Background: Acute coronary syndrome (ACS) and acute heart failure (AHF) are severe medical conditions that are closely associated with higher rates of readmissions and mortality in hospitals. These conditions pose an exponential challenge to the healthcare system and increase patient burden. Objectives: This study aims to identify the effect of telephonic follow-up on readmission and mortality rates in Rashid Hospital due to ACS and AHF. Methods: In 2022, we conducted a prospective study. We divided 805 patients admitted with ACS and AHF in Rashid Hospital into two groups and compared the readmission and mortality rates of patients who were followed up with those who were not. The data collection tool included a demographic questionnaire, which was then analyzed by statistical tests and SPSS software. Results: There were patients in the follow-up call group versus patients in the nonfollow- up call group. The patients with follow-up calls had a higher survival rate (98.3%) compared with the ones who had not been called (93.4%) (p = 0.003). Readmission rates for follow-up patients were (7.7%) versus (5.9%) for those without follow-up calls (p = 0.429). The study analyzed and investigated the individuals on various other factors; however, no statistically significant difference was observed between the two groups. Conclusion: The study provides insight into the various factors associated with patients’ outcomes. Even though the association of readmission rate to follow-up was unremarkable, the mortality rate of patients with follow-up was significantly lower.